Polyacrylate aqueous dispersion, cellulose-based reinforced diaphragm as well as preparation method and application of cellulose-based reinforced diaphragm

By coating the aqueous polyacrylate dispersion on the cellulose-based separator, the shortcomings of the cellulose-based separator in terms of mechanical strength, thermal stability and compatibility are solved, and higher mechanical properties, heat resistance and lyophilization are achieved, and the comprehensive performance of lithium batteries is improved.

CN119799111APending Publication Date: 2025-04-11GUANGZHOU CHEM CO LTD CHINESE ACADEMY OF SCI +3
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411642355.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing cellulose-based battery separators have shortcomings in terms of mechanical strength, thermal stability and compatibility, and cannot fully meet the requirements of high-energy-density batteries.

Method used

The aqueous polyacrylate dispersion is used as the reinforced coating, and components A and B are obtained by solution copolymerization and emulsion copolymerization, which are used to enhance the mechanical properties of the cellulose film and the electrolyte affinity respectively.

Benefits of technology

The mechanical properties, heat resistance and lyophilicity of the cellulose-based reinforced separator are significantly improved, the heat shrinkage rate is reduced, the electrolyte absorption rate and circulation stability are improved, thereby improving the safety performance and energy efficiency of lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119799111A_ABST
    Figure CN119799111A_ABST
Patent Text Reader

Abstract

The invention relates to the field of lithium battery diaphragms, and discloses a polyacrylate aqueous dispersion, a cellulose-based reinforced diaphragm as well as a preparation method and application of the cellulose-based reinforced diaphragm. The polyacrylate aqueous dispersion comprises a component A and a component B, the component A is obtained by solution copolymerization of a polar monomer, the component B is obtained by emulsion copolymerization of a non-polar monomer and a polar monomer, and the mass ratio of the component A to the component B is 1: 0.5-1: 2. The cellulose-based reinforced diaphragm is composed of a cellulose membrane base material and a reinforced coating, and the coating is a polyacrylate aqueous dispersion and is coated on at least one surface of the cellulose membrane base material. The diaphragm is excellent in mechanical performance, heat resistance and electrolyte affinity, the thermal shrinkage rate is as low as 0-2%, the electrolyte absorption rate is higher than 140%, the diaphragm is suitable for improving the stability of a lithium battery structure, the cycle life is prolonged, and the safety performance and the energy efficiency of the battery are remarkably improved. The material and the solvent are environment-friendly, and the preparation method is simple and suitable for large-scale application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a polyacrylate aqueous dispersion, a cellulose-based reinforced diaphragm, and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are widely used in electric vehicles, energy storage and other fields due to their advantages such as high energy density and long cycle life. Among them, the diaphragm is a key component in the battery. It serves as a physical barrier between the electrodes to prevent short circuits and provides an efficient transmission channel for electrolyte ions through its nano-scale microporous structure. In particular, the thermal stability and mechanical strength of the diaphragm play a vital role in battery performance. Although traditional polyolefin-based diaphragms have good mechanical strength, they are prone to shrinkage and melting at high temperatures, and there is a greater risk of thermal runaway. In contrast, cellulose-based diaphragms have become a potential alternative material due to their wide sources, environmental protection and excellent hydrophilicity. The lyophilicity of cellulose diaphragms helps the conduction of electrolyte ions and improves the ionic conductivity and cycle performance of the battery. However, cellulose diaphragms are insufficient in mechanical strength and thermal stability and cannot fully meet the requirements of high energy density batteries. To further solve the above technical problems, the mechanical strength and thermal stability of the diaphragm can be effectively enhanced by coating functional polymer materials (such as polyvinylidene fluoride, polyacrylate, etc.) on the cellulose diaphragm. However, the electrolyte affinity and environmental friendliness of polyvinylidene fluoride are poor, and it is also not conducive to compatibility with cellulose substrates. Commercially available polyacrylates are mostly non-polar hard and soft monomers, which can be used to increase the strength of cellulose diaphragms, but the prepared cellulose diaphragms still have the problem of insufficient conductivity. CN111326697A is by coating a coating composition on a diaphragm substrate, and the combination includes ceramic particles, nanocellulose fibers, temperature-sensitive particles, dispersants, binders and aqueous solvents, and the coating contains high-temperature resistant ceramic particles and nanocellulose fibers, and the nanocellulose fibers can form a cross-linked structure of a stable three-dimensional network in the coating, which improves high-temperature resistance and improves mechanical properties at the same time. Although there are complex particle fillers in the coating, it is conducive to enhancing various performances, but it may be due to the poor adhesion of particles, clogging pores and uneven dispersion, etc., resulting in ionic conductivity, structural stability and cycle life. CN207250624U is by coating polyvinylidene fluoride and acrylate to enhance the performance of polyolefin diaphragms, but the poor compatibility of the coating and the diaphragm itself can only act on the surface, which is not conducive to the optimization of the internal performance of the membrane. Therefore, providing a cellulose-based reinforced separator to improve the current technical problems of cellulose battery separators such as poor extrusion and puncture resistance, heat resistance and compatibility and to improve the energy efficiency of the battery has broad application prospects. Summary of the invention

[0003] In view of the problems existing in the prior art, the primary purpose of the present invention is to provide an aqueous polyacrylate dispersion.

[0004] Another object of the present invention is to provide a cellulose-based reinforced separator.

[0005] Another object of the present invention is to provide a method for preparing a cellulose-based reinforced separator.

[0006] Another object of the present invention is to provide application of the above cellulose-based reinforced separator.

[0007] The purpose of the present invention is achieved through the following technical solutions:

[0008] A polyacrylate aqueous dispersion comprises component A and component B, wherein component A is obtained by solution copolymerization of a polar monomer, and component B is obtained by emulsion copolymerization of a non-polar monomer and a polar monomer.

[0009] Preferably, the mass ratio of component A to component B is 1:0.5 to 1:2.

[0010] Preferably, the polar monomer of component A includes acrylic acid monomer and at least two of the following monomers: acrylonitrile, acrylamide, β-acryloxypropionic acid and vinyl acetate.

[0011] Preferably, the mass percentage of acrylic acid monomer in component A to polar monomer is 30-80%.

[0012] Preferably, the preparation steps of component A are as follows: polar monomers are mixed to obtain a mixed monomer, a neutralizer is added to the mixed monomer to neutralize about 50% of the carboxyl groups, a solvent and an initiator are added, solution copolymerization is performed in a deoxygenated environment, and component A is adjusted to neutrality after polymerization.

[0013] The neutralizing agent is LiOH;

[0014] The initiator is ammonium persulfate or potassium persulfate, the added amount of the initiator is 0.5-1% of the total mass of the mixed monomers, and the solvent is water.

[0015] The temperature of the solution copolymerization is 65-80°C.

[0016] Preferably, the polar monomer of component B includes at least one of the following monomers: acrylic acid, methacrylic acid and β-acryloxypropionic acid, and the non-polar monomer includes at least two of the following monomers: methyl methacrylate, ethyl acrylate, butyl acrylate, isooctyl acrylate and styrene.

[0017] Preferably, the mass percentage of the polar monomer in the component B is 10% to 20%.

[0018] Preferably, the preparation steps of component B are as follows: premixing polar monomers and non-polar monomers to obtain premixed monomers, adding emulsifiers and dispersant water and emulsifying to obtain pre-emulsion, adding initiators to part of the pre-emulsion to obtain seed pre-emulsion, heating and performing seed emulsion polymerization in a deoxygenated environment, then dripping the remaining pre-emulsion and heating again to perform subsequent emulsion polymerization reaction to obtain component B.

[0019] Furthermore, during the seed emulsion polymerization, the amount of emulsion used is 40-50wt% of the pre-emulsion, the temperature is 65-75°C, and the time is 10-30 minutes.

[0020] Furthermore, the remaining pre-emulsion is added dropwise for 1 to 2 hours at a temperature of 70 to 85° C. for 2 to 3 hours.

[0021] Preferably, the emulsifier is at least one of nonylphenol polyoxyethylene ether-10 (OP-10) and sodium dodecylbenzene sulfonate (SDBS), and the added amount is 4-8% of the total mass of the premixed monomers; the initiator is ammonium persulfate or potassium persulfate, and the added amount is 0.5-1% of the total mass of the premixed monomers.

[0022] A cellulose-based reinforced diaphragm comprises a cellulose film substrate and a reinforced coating, wherein the reinforced coating is the above-mentioned polyacrylate aqueous dispersion, which is coated on at least one side of the cellulose film substrate.

[0023] Preferably, the cellulose film substrate is selected from one of the following microporous films: regenerated cellulose film, cellulose acetate film, ethyl cellulose film, carboxymethyl cellulose film.

[0024] The method for preparing the above-mentioned cellulose-based reinforced separator comprises the following steps:

[0025] (1) preparing the aqueous polyacrylate dispersion: mixing component A and component B according to the proportion, appropriately diluting and fully stirring to make the dispersion uniform and stable;

[0026] (2) Preparation of reinforced membrane: The cellulose membrane substrate and the aqueous polyacrylate dispersion are combined by coating, and the aqueous polyacrylate dispersion is solidified on the surface of the substrate by drying, and then washed and dried again to a constant weight to obtain a cellulose-based reinforced membrane.

[0027] Preferably, the diluent used in the dilution in step (1) is a mixture of deionized water and anhydrous ethanol, and the volume fraction of ethanol is 20 vol% to 50 vol%.

[0028] The stirring rate in step (1) is 100 rpm to 500 rpm, and the stirring time is 10 to 15 hours.

[0029] The solid content of the dispersion in step (1) is 3-30%, and the pH is 6-8.

[0030] Preferably, the dispersion obtained in step (1) is allowed to stand for degassing under vacuum conditions at room temperature for later use.

[0031] Preferably, the coating method in step (2) is one of dip coating, spin coating, roller coating or wire rod coating.

[0032] The drying in step (2) is vacuum drying, the temperature is 80-100° C., the vacuum treatment time is 3-5 hours, and the vacuum degree is -0.0999 to -0.093 MPa.

[0033] The washing liquid in step (2) is a mixture of deionized water and anhydrous ethanol, the volume fraction of ethanol is 20 vol% to 50 vol%, and the washing method is flushing or ultrasonic washing.

[0034] The step (2) of drying again after washing is vacuum drying, the temperature is 40 to 60° C., the vacuum treatment time is 1 to 2 hours, and the vacuum degree is -0.0999 to -0.093 MPa.

[0035] Preferably, excess dispersion on the surface is removed promptly after coating to prevent the excessive dispersion from solidifying and clogging the pores.

[0036] The above-mentioned cellulose-based reinforced separator is used in lithium-ion batteries.

[0037] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0038] (1) The polyacrylate aqueous dispersion strengthener used in the present invention has excellent water-based dispersibility and good compatibility with cellulose substrates, which is conducive to coating reinforcement. At the same time, the dispersion has a large amount of polar monomers, and the formation of a hydrogen bond network is conducive to strengthening the mechanical properties and heat resistance of the cellulose substrate. In addition, the rich carboxyl and cyano groups are conducive to improving the electrolyte affinity and ion conductivity of the diaphragm. Finally, the ratio of non-polar monomers to polar monomers makes it easy to regulate the rigidity, flexibility and adhesion of the diaphragm, which is suitable for various types of application scenarios.

[0039] (2) The cellulose-based reinforced diaphragm obtained by the present invention has better mechanical properties, heat resistance and lyophilicity, a heat shrinkage rate as low as 0-2%, and an electrolyte absorption rate higher than 140%. Since the polyacrylate copolymer on its surface has adhesiveness, it is conducive to the mutual adhesion of the battery structure during the battery assembly process, enhancing the structural stability and cycle stability of the battery, thereby improving the safety performance of the lithium battery, and is conducive to improving the cycle life and energy efficiency of the lithium battery.

[0040] (3) The present invention does not use harmful organic solvents in the process of preparing the cellulose-based reinforced diaphragm, which completely avoids the emission and recovery of organic pollutants, is safe and environmentally friendly, and at the same time, the raw materials are easily available and the process is simple, which has the advantages of economy and is suitable for large-scale application. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is a scanning electron microscope image of the reinforced diaphragm prepared in Example 3 of the present invention.

[0042] Figure 2 It is a scanning electron microscope image of the cellulose separator selected in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0043] The present invention is further described in detail below in conjunction with the examples, but the embodiments of the present invention are not limited thereto. Based on the examples of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention, and for process parameters not specifically noted, conventional techniques may be used.

[0044] Embodiment 1:

[0045] (1) Preparing a polyacrylate aqueous dispersion: Component A and Component B are mixed in a ratio of 1:1. Component A comprises 30% acrylic acid, 30% acrylonitrile, 20% acrylamide and 20% vinyl acetate (by mass percentage). Component A is obtained by solution copolymerization of polar monomers. The polar monomers are mixed to obtain a mixed monomer. A neutralizing agent LiOH is added to the mixed monomer to neutralize about 50% of the carboxyl groups. Then, solvent water and an initiator ammonium persulfate are added in an amount of 0.5% of the total mass of the mixed monomer. The copolymerization reaction is carried out under nitrogen protection at a copolymerization temperature of 70° C. After polymerization, the entire component A is adjusted to be neutral. The monomer composition of component B is 20% acrylic acid, 40% methyl methacrylate, and 40% styrene (by mass percentage). Component B is obtained by emulsion copolymerization of non-polar monomers and polar monomers. The non-polar monomers and polar monomers are mixed to obtain pre-mixed monomers, and emulsifiers and dispersant water are added. The emulsifiers are OP-10 and SDBS (mass ratio 2:1), and the addition amount is 5% of the total mass of the pre-mixed monomers. Emulsification is carried out at 2000rpm for 30 minutes to obtain a pre-emulsion. Take 50% of the pre-emulsion, add initiator ammonium persulfate under nitrogen protection, and the addition amount is 0.5% of the total mass of the pre-mixed monomers. Seed emulsion polymerization is carried out in a deoxygenated environment for 20 minutes, and the polymerization temperature is 75°C, and then heated to 85°C. The remaining pre-emulsion is added dropwise within 2 hours and the polymerization reaction is kept warm for 1 hour. After polymerization, the entire component B is adjusted to neutral. Component A and component B are mixed, appropriately diluted, stirred and mixed at 500rpm for 10 hours, and vacuum degassed for standby use. The pH value of the polyacrylate aqueous dispersion after stabilization was 8, and the solid content of the dispersion was 10%.

[0046] (2) Preparation of reinforced diaphragm: A cellulose acetate film substrate and a prepared aqueous dispersion were selected and combined by wire rod coating. After coating, the excess dispersion on the surface was removed in time, and the vacuum treatment time was 5 h at 100 ° C, and the vacuum degree was -0.0999 MPa. After curing, 30 vol% ethanol was used for ultrasonic washing, and vacuum dried at 50 ° C for 2 h to constant weight to obtain a cellulose-based reinforced lithium battery diaphragm with a diaphragm thickness of 182 μm and a coating thickness of about 20 μm.

[0047] Embodiment 2:

[0048] (1) Preparing a polyacrylate aqueous dispersion: Component A and component B are mixed in a ratio of 1:0.5. Component A comprises 30% acrylic acid, 40% acrylamide and 30% β-acryloxypropionic acid (by mass percentage). Component A is obtained by solution copolymerization of polar monomers. The polar monomers are mixed to obtain a mixed monomer. A neutralizing agent LiOH is added to the mixed monomer to neutralize about 50% of the carboxyl groups. Then, solvent water and initiator ammonium persulfate are added in an amount of 0.5% of the total mass of the mixed monomer. The copolymerization process is carried out under nitrogen protection at a copolymerization temperature of 65° C. After polymerization, the entire component A is adjusted to be neutral. The monomer composition of component B is 10% acrylic acid, 10% methacrylic acid, 40% butyl acrylate and 40% methyl methacrylate (by mass percentage). Component B is obtained by emulsion copolymerization of non-polar monomers and polar monomers. The non-polar monomers and polar monomers are mixed to obtain pre-mixed monomers, and emulsifiers and dispersant water are added. The emulsifiers are OP-10 and SDBS (mass ratio 2:1), and the addition amount is 5% of the total mass of the pre-mixed monomers. Emulsification is carried out at 2000rpm for 30 minutes to obtain a pre-emulsion. Take 50% of the pre-emulsion, add initiator ammonium persulfate under nitrogen protection, and the addition amount is 0.5% of the total mass of the pre-mixed monomers. Seed emulsion polymerization is carried out in a deoxygenated environment for 20 minutes, and the polymerization temperature is 75°C, and then heated to 85°C. The remaining pre-emulsion is added dropwise within 2 hours and the polymerization reaction is kept warm for 1 hour. After polymerization, the entire component B is adjusted to neutral. Component A and component B are mixed, appropriately diluted, stirred and mixed at 200rpm for 12h, and vacuum degassed for standby use. The pH value of the polyacrylate aqueous dispersion after stabilization was 7, and the solid content of the dispersion was 5%.

[0049] (2) Preparation of reinforced diaphragm: The regenerated cellulose film substrate and the prepared aqueous dispersion were combined by roller coating. After roller coating, the excess dispersion on the surface was removed in time, and the vacuum treatment time was 5 h at 80 ° C, and the vacuum degree was -0.0999 MPa. After curing, 20 vol% ethanol was used for ultrasonic washing, and vacuum dried at 50 ° C for 2 h to constant weight to obtain a cellulose-based reinforced lithium battery diaphragm with a diaphragm thickness of 169 μm and a coating thickness of about 10 μm.

[0050] Embodiment 3:

[0051] (1) Preparing a polyacrylate aqueous dispersion: Component A and Component B are mixed in a ratio of 1:1. Component A has a monomer composition of 40% acrylic acid, 40% acrylonitrile and 20% acrylamide (by mass percentage). Component A is obtained by solution copolymerization of polar monomers. Each polar monomer is mixed to obtain a mixed monomer. A neutralizing agent LiOH is added to the mixed monomer to neutralize about 50% of the carboxyl groups. Then, solvent water and an initiator potassium persulfate are added in an amount of 0.5% of the total mass of the mixed monomer. Solution copolymerization is carried out under nitrogen protection at a copolymerization temperature of 70° C. After polymerization, the entire component A is adjusted to be neutral. The monomer composition of component B is 20% acrylic acid, 40% ethyl acrylate and 40% methyl methacrylate (by mass percentage). Component B is obtained by emulsion copolymerization of non-polar monomers and polar monomers. The non-polar monomers and polar monomers are mixed to obtain pre-mixed monomers, and emulsifiers and dispersant water are added. The emulsifiers are OP-10 and SDBS (mass ratio 2:1), and the addition amount is 6% of the total mass of the pre-mixed monomers. The pre-emulsion is obtained by emulsification at 2000rpm for 30 minutes. Take 50% of the pre-emulsion, add initiator ammonium persulfate under nitrogen protection, and the addition amount is 0.5% of the total mass of the pre-mixed monomers. Seed emulsion polymerization is carried out in a deoxygenated environment for 20 minutes, and the polymerization temperature is 75°C, and then heated to 85°C. The remaining pre-emulsion is added dropwise within 2 hours and the polymerization reaction is kept warm for 1 hour. After polymerization, the entire component B is adjusted to neutral. Component A and component B are mixed, appropriately diluted, stirred and mixed at 300rpm for 12h, and vacuum degassed for standby use. The pH value of the polyacrylate aqueous dispersion after stabilization was 8, and the solid content of the dispersion was 3%.

[0052] (2) Preparation of reinforced diaphragm: The regenerated cellulose film substrate and the prepared aqueous dispersion were combined by dip coating. After dip coating, the excess dispersion on the surface was removed in time, and the vacuum treatment time was 3 h at 100 ° C, and the vacuum degree was -0.0999 MPa. After curing, it was rinsed with 20 vol% ethanol and vacuum dried at 50 ° C for 2 h to constant weight to obtain a cellulose-based reinforced lithium battery diaphragm with a diaphragm thickness of 175 μm and a coating thickness of about 15 μm.

[0053] Figure 1 The scanning electron microscope image of the reinforced separator prepared in Example 3 is compared with the unmodified cellulose separator ( Figure 2 ) can be found in Figure 1 The formation of a polymer protective shell was clearly found on the surface of the diaphragm, wrapping the substrate. In addition, it can be found that the polymer functional layer not only acts on the surface but also enters the internal pores of the substrate, indicating the good compatibility of the dispersion with the cellulose substrate.

[0054] Embodiment 4:

[0055] (1) Preparing a polyacrylate aqueous dispersion: Component A and component B are mixed in a ratio of 1:2. Component A has a monomer composition of 40% acrylic acid, 40% acrylonitrile and 20% acrylamide (by mass percentage). Component A is a polar monomer obtained by solution copolymerization. Each polar monomer is mixed to obtain a mixed monomer. A neutralizing agent LiOH is added to the mixed monomer to neutralize about 50% of the carboxyl groups. Then, solvent water and an initiator potassium persulfate are added in an amount of 0.5% of the total mass of the mixed monomer. Solution copolymerization is carried out under nitrogen protection at a copolymerization temperature of 65° C. After polymerization, the entire component A is adjusted to be neutral. The monomer composition of component B is 10% acrylic acid, 10% methacrylic acid, 40% butyl acrylate and 40% methyl methacrylate (by mass percentage). Component B is obtained by emulsion copolymerization of non-polar monomers and polar monomers. The non-polar monomers and polar monomers are mixed to obtain pre-mixed monomers, and emulsifiers and dispersant water are added. The emulsifiers are OP-10 and SDBS (mass ratio 2:1), and the addition amount is 5% of the total mass of the pre-mixed monomers. Emulsification is carried out at 2000rpm for 30 minutes to obtain a pre-emulsion. Take 50% of the pre-emulsion, add initiator ammonium persulfate under nitrogen protection, and the addition amount is 0.5% of the total mass of the pre-mixed monomers. Seed emulsion polymerization is carried out in a deoxygenated environment for 20 minutes, and the polymerization temperature is 75°C, and then heated to 85°C. The remaining pre-emulsion is added dropwise within 2 hours and the polymerization reaction is kept warm for 1 hour. After polymerization, the entire component B is adjusted to neutral. Component A and component B are mixed, appropriately diluted, stirred and mixed at 200rpm for 10 hours, and vacuum degassed for standby use. The pH value of the polyacrylate aqueous dispersion after stabilization was 8, and the solid content of the dispersion was 3%.

[0056] (2) Preparation of reinforced diaphragm: The regenerated cellulose film substrate and the prepared aqueous dispersion were combined by dip coating. After dip coating, the excess dispersion on the surface was removed in time, and the vacuum treatment time was 3 h at 100 ° C, and the vacuum degree was -0.0999 MPa. After curing, it was rinsed with 20 vol% ethanol and vacuum dried at 50 ° C for 2 h to constant weight to obtain a cellulose-based reinforced lithium battery diaphragm with a diaphragm thickness of 185 μm and a coating thickness of about 25 μm.

[0057] Comparative Example 1:

[0058] This example provides a diaphragm, which is a single-layer structure and a microporous regenerated cellulose film with a thickness of 160 μm. Figure 2 It can be seen that the initial cellulose membrane has a multi-layer microporous structure, while the modified membrane ( Figure 1 ) Its pore size is relatively large, and this structure is prone to cause the formation of lithium dendrites during long-term use and lead to a decrease in cycle stability.

[0059] Comparative Example 2:

[0060] This example provides a diaphragm, which has a single-layer structure and is a microporous commercial polypropylene film with a thickness of 26 μm.

[0061] Comparative Example 3:

[0062] In this example, a regenerated cellulose film substrate and component A in Example 3 were combined by dip coating. After dip coating, the excess component A on the surface was removed in time, and the vacuum treatment time was 2 hours at 80°C, and the vacuum degree was -0.0999MPa. After curing, it was rinsed with 10vol% ethanol and vacuum dried at 50°C for 2 hours to constant weight to obtain a cellulose-based reinforced lithium battery separator with a separator thickness of 166μm and a coating thickness of about 5μm. Comparative Example 4:

[0063] In this example, the regenerated cellulose film substrate and the component B in Example 3 were combined by dip coating. After dip coating, the excess component B on the surface was removed in time, and the vacuum treatment time was 2 hours at 100°C, and the vacuum degree was -0.0999MPa. After curing, it was rinsed with 20vol% ethanol and vacuum dried at 50°C for 2 hours to constant weight to obtain a cellulose-based reinforced lithium battery separator with a separator thickness of 171 μm and a coating thickness of about 10 μm. Diaphragm performance test:

[0064] Test the various properties of the diaphragm: The diaphragms obtained in Examples 1-3 and Comparative Examples 1-2 include tensile and puncture resistance, heat resistance, electrolyte absorption rate, porosity, etc. Among them, the tensile resistance is carried out according to the description of GB / T1040.1-2018, and the puncture resistance is carried out according to the description of GB / T 37841-2019. The heat resistance is to cut the obtained diaphragm into original sheets and treat them at 150°C for 1 hour, and record their dimensional shrinkage.

[0065] The porosity of the membrane was determined by n-butanol adsorption test and calculated by the following formula:

[0066]

[0067] where w w and w d are the weights of wet and dry films after immersion in n-butanol for 2 h, ρ b is the density of n-butanol, and V is the geometric volume of the membrane.

[0068] The absorbance of the liquid electrolyte was measured by immersing the weighed separator in the liquid electrolyte in an argon-filled glove box at room temperature. The electrolyte absorbance (EU) was calculated according to the following formula:

[0069]

[0070] Where w0 and w1 are the mass of the membrane before and after immersion in liquid LiPF6 electrolyte for 2 h. The final P and EU are determined based on the average values ​​of 5 samples. All test results are summarized in Table 1.

[0071] Preparation of lithium battery: The separator obtained in Examples 1-4 and Comparative Examples 1-4 was assembled with a positive electrode, a negative electrode and an electrolyte to form a button cell. The positive electrode material was lithium iron phosphate (nominal specific capacity of 150 mAh / g), the negative electrode was natural graphite, the electrolyte was 1M lithium hexafluorophosphate, and the solvent was ethylene carbonate / dimethyl carbonate / ethyl methyl carbonate (volume ratio 1:1:1). The average discharge specific capacity and capacity retention rate within 100 cycles were recorded by 1C constant current charge and discharge cycle test, and all test results are summarized in Table 1.

[0072] Table 1 Diaphragm composition and performance test results

[0073]

[0074] It can be clearly seen from Table 1 that Examples 1-4 of the present invention have obvious comprehensive performance improvements compared with Comparative Example 1. Among them, Example 1 has better tensile and puncture resistance and lower thermal shrinkage than the examples, indicating that it has better mechanical strength and good thermal stability. Example 2 has higher porosity and electrode liquid absorption rate than the examples, indicating that it has wettability and high electrolyte affinity. Compared with Comparative Example 1, Example 3 has improved performance in all aspects except porosity, and has a higher cycle specific capacity, that is, higher energy efficiency and better comprehensive performance. By comparing with the mature commercial membrane Comparative Example 2, it can be found that cellulose membranes have better thermal stability and electrolyte affinity, and the advantages of Examples 1-4 in this regard are more obvious after being strengthened by the present invention.

[0075] Most commercially available polyacrylates contain only non-polar soft and hard monomers, which can be used to increase strength and heat resistance, but have limited effect on increasing ion conductivity. When the coating includes only component A, the heat resistance and strength of the copolymer-reinforced cellulose membrane are limited (Comparative Example 3), while when only component B is included, the ion conductivity and electrochemical stability of the copolymer-reinforced cellulose membrane are limited (Comparative Example 4). When the mass ratio of components A and B differs too much (not in the range of 1:0.5 to 1:2), the strengthening effect of the copolymer coating will also be unbalanced, which is similar to the effect of using A or B alone.

[0076] The functional monomers in component A need to play the role of enhancing ion conduction and electrochemical stability respectively, so at least two or more monomers are needed. Adding only one will only have limited effect. When there is only one of them in component B, using only rigid and flexible monomers is not conducive to improving the mechanical properties and heat resistance of the diaphragm. Adding an inappropriate amount of polar monomers is not conducive to the emulsion polymerization process, nor is it conducive to the compatibility of subsequent components A and B. Therefore, at least two or more monomers are required.

[0077] The cellulose-based reinforced diaphragm of the present invention has good thermal stability and lyophilicity, and effectively improves the mechanical properties and cycle stability of the diaphragm. It also has the advantages of a wide range of material sources and a simple preparation process, thus reflecting potential economic value.

[0078] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A polyacrylate aqueous dispersion, characterized in that: The invention comprises component A and component B, wherein the component A is obtained by solution copolymerization of polar monomers, and the component B is obtained by emulsion copolymerization of non-polar monomers and polar monomers.

2. The aqueous polyacrylate dispersion according to claim 1, characterized in that The mass ratio of component A to component B is 1:0.5 to 1:

2.

3. The aqueous polyacrylate dispersion according to claim 1, characterized in that: The polar monomer of component A includes acrylic acid monomer and at least two of the following monomers: acrylonitrile, acrylamide, β-acryloxypropionic acid and vinyl acetate; The mass percentage of acrylic acid monomer to polar monomer is 30-80%.

4. The aqueous polyacrylate dispersion according to claim 1, characterized in that The polar monomer of component B includes at least one of the following monomers: acrylic acid, methacrylic acid and β-acryloxypropionic acid; The non-polar monomer includes at least two of the following monomers: methyl methacrylate, ethyl acrylate, butyl acrylate, isooctyl acrylate and styrene.

5. The aqueous polyacrylate dispersion according to claim 1, characterized in that: The mass percentage of the polar monomer in the component B is 10-20%.

6. A cellulose-based reinforced separator, characterized in that: The invention comprises a cellulose film substrate and a strengthening coating, wherein the strengthening coating is obtained by coating the polyacrylate aqueous dispersion according to any one of claims 1 to 5 on at least one side of the cellulose film substrate.

7. The cellulose-based reinforced separator according to claim 6, characterized in that: The cellulose film substrate is selected from one of the following microporous films: regenerated cellulose film, cellulose acetate film, ethyl cellulose film, and carboxymethyl cellulose film.

8. The method for preparing the cellulose-based reinforced separator according to claim 6 or 7, characterized in that: The steps include: (1) preparing the aqueous polyacrylate dispersion: mixing component A and component B according to the proportion, appropriately diluting and fully stirring to make the dispersion uniform and stable; (2) Preparation of reinforced diaphragm: The cellulose film substrate and the aqueous polyacrylate dispersion are combined by coating, and the aqueous polyacrylate dispersion is solidified on the surface of the substrate by drying, and then washed and dried again to a constant weight to obtain a cellulose-based reinforced diaphragm.

9. The method for preparing a cellulose-based reinforced separator according to claim 8, characterized in that: The coating method described in step (2) is one of dip coating, spin coating, roller coating or wire rod coating.

10. Use of the cellulose-based reinforced separator according to claim 6 or 7 in lithium-ion batteries.

Citation Information

Patent Citations

  • Coated diaphragm and preparation method thereof

    CN111326697A

  • Lithium ion battery is with two -sided bonding diaphragm and lithium ion battery

    CN207250624U